2009
DOI: 10.1177/0218492309343857
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Chronic Total Occlusion of the Left Main Stem: A 10-Year Experience

Abstract: Chronic total occlusion of the left main stem coronary artery is rare. This retrospective study was conducted to evaluate outcomes of coronary artery bypass grafting between June 1998 and June 2008 in patients with chronic left main stem total occlusion. There were 17 (0.025%) cases detected in 67,082 coronary angiograms. The 14 men and 3 women had a mean age of 55.32 +/- 9.2 years. Risk factors included diabetes in 8, hypertension in 6, and smoking in 6. Of 54 grafts applied, 15 were arterial and 39 were veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This type of chronic occlusion in the LMT is rare, occurring in only 0.025–0.4% of ischemic heart disease patients [ 2 ]. In our hospital, from April 2014 to March 2015, coronary angiography was performed 3 841 times at our hospital for patients suspected of having ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of chronic occlusion in the LMT is rare, occurring in only 0.025–0.4% of ischemic heart disease patients [ 2 ]. In our hospital, from April 2014 to March 2015, coronary angiography was performed 3 841 times at our hospital for patients suspected of having ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, chronic total occlusion (CTO) has an asymptomatic period, and when diagnosed its symptoms are often slight. CTO of the LMT is an extremely rare pathology, observed in only 0.025–0.4% of patients who undergo coronary angiography [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that coronary chronic total occlusion (CTO) is encountered in 15 to 20% of patients referred for coronary angiography (CAG). Chronic total occlusion of left main coronary artery (LMCA) is rare on the angiograms and is described as a total lack of antegrade blood flow to the coronary arteries with retrograde collateral circulation [1,11]. Under these conditions, most of the myocardium is under ischemic stress, which is associated with high mortality.…”
Section: Cardiovascularmentioning
confidence: 99%
“…[47][48][49] Successful revascularization rates are reported at 80% to 90% for CTOs of the left circumflex artery, with >80% of patients having all multiple CTOs treated successfully and concomitantly. 23,36 Fefer et al 36 showed that the presence of CTOs was not associated with increased mortality by multivariate analysis.…”
Section: Efficacy Of Cabg For Ctos Affecting Coronary Vessels Other Tmentioning
confidence: 99%